ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN MENGGUNAKAN METODE ANALYTICAL HIERARCHI PROCCES (AHP) PADA PT.SIERRA SOLUTIONS INDONESIA JAMBI - Triadi, Albet; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2019)
In the process of defining position , indispensable a system supporting decisions measurable as in PT.Sierra Solutions Indonesia Jambi east where have a system supporting decisions measurable indetermining Employee acceptance.There should have been criteria support to use the supporting decision.In this research using method AHP (Analytical Hierachi Proces) to ease in taking a decision .With thesystem of methods Analytical Hierachi Proces by looking for the weighted sum of Critria in eachalternative on all attributes